Life Modifications and PCOS: Old Story But New Tales - Gu, Yuanyuan; Zhou, Guannan; Zhou, Fangyue; Wu, Qiongwei; Ma, Chengbin; Zhang, Yi; Ding, Jingxin; Hua, Keqin (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome (PCOS) is defined as a kind of endocrine and metabolic disorder that affects female individuals of reproductive age. Lifestyle modifications, including diet modifications, exercise, and behavioral modification, appear to alleviate the metabolic dysfunction and improve the reproductive disorders of PCOS patients (particularly in obese women). Therefore, lifestyle modifications have been gradually acknowledged as the first-line management for PCOS, especially in obese patients with PCOS. However, the mechanism of lifestyle modifications in PCOS, the appropriate composition of diet modifications, and the applicable type of exercise modifications for specific female populations are rarely reported. We conducted a systematic review and enrolled 10 randomized controlled trials for inclusion in a certain selection. In this review, we summarized the existing research on lifestyle modifications in PCOS. We aimed to illustrate the relationship between lifestyle modifications and PCOS (referring to hyperandrogenism, insulin resistance as well as obesity) and also considered the priorities for future research. These results might be an invaluable tool to serve as a guide in lifestyle modifications as the intervention for PCOS and other related endocrine disorders.